Metareasoning : thinking about thinking - Cox, Michael T., 1955-; Raja, Anita, 1975- (MIT Press, 2011)
This text offers a simple model of reasoning about reason as a framework for its discussions. Following this framework, the contributors consider meta-level control of computational activities, introspective monitoring, distributed meta-reasoning, and, putting all these aspects of meta- reasoning together.